Violent couples seeking therapy: bilateral and unilateral violence - Madsen, C.; Stith, Sandra M.; Thomsen, C.; McCollum, E. (My University, 2012)
Little information is available about couples experiencing Intimate Partner Violence (IPV) who voluntarily seek couples therapy. We examined the characteristics of 129 couples who sought therapy for IPV to learn more about this population. A majority of the sample, 74%, experienced bilateral physical violence, 16% experienced unilateral male violence, and 5% experienced unilateral female violence. Conflict theory is used to explain the finding that couples experiencing bilateral violence reported higher levels of physical violence and injury than did those experiencing unilateral violence. Bilaterally violent couples also experienced more jealousy and psychological aggression and less relationship satisfaction than either group of unilaterally violent couples. Implications and suggestions for clinicians are offered, as well as ideas for future research.
Keywords: Intimate partner violence; Therapy‐seeking; Bilateral violence; Unilateral violence